2018
DOI: 10.1002/jrs.5355
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive VOC gas sensor employing deep cooling of SERS film

Abstract: The potential of surface‐enhanced Raman spectroscopy (SERS) as a highly sensitive and selective gas sensor was investigated experimentally. Especially, the relation between the temperature of a SERS film and gas adsorption or signal intensity was observed systemically and quantitatively, from which the enhancement of gas adsorption and signal intensity by up to 40 times was observed with the SERS film temperature of approx. −80 °C, which corresponds to theoretical anticipation and leads to detection sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…SERS can also expand its utilization from the aquatic environment to the vapor phase which should find applications in chemical sensing for volatile organic chemicals and explosives (Shah et al, 2013; Kreno et al, 2014; He et al, 2015; Ma et al, 2016b; Oh et al, 2018). Ma et al designed a real-time gas sensing platform for 2-naphthalenethiol (2-NaT) and 2-mercaptopyridine (2-MPy) employing AgNRs-HfO 2 substrates (Ma et al, 2016b).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…SERS can also expand its utilization from the aquatic environment to the vapor phase which should find applications in chemical sensing for volatile organic chemicals and explosives (Shah et al, 2013; Kreno et al, 2014; He et al, 2015; Ma et al, 2016b; Oh et al, 2018). Ma et al designed a real-time gas sensing platform for 2-naphthalenethiol (2-NaT) and 2-mercaptopyridine (2-MPy) employing AgNRs-HfO 2 substrates (Ma et al, 2016b).…”
Section: Applicationsmentioning
confidence: 99%
“…Thus, various molecules modifications on plasmonic materials were explored by researchers, such as metal–organic frameworks and thiol compounds (Lee et al, 2019). For example, Oh et al fabricated AgNRs and functionalized it with propanethiol (Oh et al, 2018). Due to the physical adsorption of benzene molecules to propanethiol, SERS spectra of benzene in vapor phase were successfully observed on substrates and the detection ability of this sensor was found ~1 ppm at room temperature with 120 s acquisition time.…”
Section: Applicationsmentioning
confidence: 99%
“…Oh and co‐workers explored the potential of SERS as a highly sensitive and selective gas sensor. Of special focus was the relation between the temperature of the SERS film and gas adsorption from which the enhancement of gas adsorption and signal intensity by up to 40 times was observed . Piergies et al were able to identify adsorption of the pattern of erlotinib onto silver NPs using SERS.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…Of special focus was the relation between the temperature of the SERS film and gas adsorption from which the enhancement of gas adsorption and signal intensity by up to 40 times was observed. [45] Piergies et al were able to identify adsorption of the pattern of erlotinib onto silver NPs using SERS. They found that the phenyl ring interacts rather weakly with the AgNPs and is oriented perpendicularly onto the surface, whereas the quanizoline moiety only participates in this interaction with a tilted orientation.…”
Section: Sers Substratesmentioning
confidence: 99%
“…The Raman scattering signals carrying the ngerprint information of molecules with high spectral resolution and sensitivity can be applied in the elds of catalysis, 1 sensing, [2][3][4][5][6] chemical analysis, [7][8][9] environment monitoring. 10 However, the weak Raman scattering intensity of pure substances limits its scope of comprehensive application. Surface-enhanced Raman spectroscopy (SERS) is a powerful and effective non-destructive strategy to further strengthen Raman scattering.…”
Section: Introductionmentioning
confidence: 99%